PERANAN KEPERCAYAAN, KEMUDAHAN, DAN KUALITAS INFORMASI PADA KEPUTUSAN PEMBELIAN MELALUI E-COMMERCE SHOPEE MAHASISWA KOTA BANDUNG - Heryawan, Kevin Christian; Kristiawan, Allen (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Purchasing decisions play a major role in e-commerce. One of the factors that influence them is trust, convenience and information quality. The research conducted aims to investigate, test and analyze the role of trust, convenience and information quality factors in purchasing decisions. Using the causal explanation method and non-probability sampling, the population and samples used were students in Bandung City who purchased from Shopee e-commerce. Using SPSS 26 with validity test, reliability test and classical acceptance test, it was found that trust, convenience and information quality have a positive and significant effect on purchase decisions.